Biological false positive rapid plasma reagin tests in pregnant females in North India - Sahota, Somanpreet Kaur; Shakya, Barun Kumar; Arora, Deepak; Jindal, Neeraj (International Journal Of Community Medicine And Public Health, 2021)
Background: Syphilis, a sexually transmitted disease seriously complicate pregnancy and produce harmful results in fetus. Screening of pregnant females in early pregnancy with non-treponemal tests such as RPR and VDRL is a cost effective strategy for diagnosis of syphilis. However, these tests could produce BFP reaction in pregnancy. The prevalence of which may be different in different populations and at different times. The current prevalence of the biological false positive rapid plasma regain tests in pregnant females of North India was there for assessed and being reported. Methods: A total 500 consecutive pregnant females who presented to our tertiary care center for the first time were screened for syphilis by RPR (a non-treponemal test) and Hi-Quik (a treponemal test) after obtaining their written consent. Results: Of the 500 females 21 (4.2%) were RPR positive and only one (0.2%) was Hi-Quik positive. Thus the prevalence of biological false positive rapid plasma regain tests in pregnant females of North India was 4% (20/500). In semi quantitative RPR, these tests were positive in ≤1:4 dilution and were not found to be related to any particular age, geographical distribution, literacy status, occupation or period of gestation (p value >0.05) and were transient in nature. Conclusions: Our study concludes that although RPR is a good, cost effective test for mass screening of pregnant females, but it produces BFP reactions in considerable percentage (4%) in pregnant females of North India.